Growth, maturation, and physical activity - Malina, Robert M.; Bouchard, Claude; Bar-Or, Oded (Human Kinetics Books, 2004)
This edition features updates on basic content, expanded and modified chapters, and the latest research findings to meet the needs of upper undergraduate and graduate students as well as researchers and professionals working with children and young adults." "Growth, Maturation, and Physical Activity, Second Edition, covers many new topics, including techniques for the assessment of body composition, the latest advances in the study of skeletal muscle, the human genome project, the hormonal regulation of growth and maturation, clarification of dietary reference intakes, and the study of risk for several adult diseases." "This is the only text to focus on the biological growth and maturation process of children and adolescents as it relates to physical activity and performance."--Jacket